Poldip2 deficiency attenuates lung disease severity in a mouse model of COVID-19 - Ruinan Hu; Alejandra Valdivia; Taylor White; Willy Ju; Maegan L. Brockman; Zhan Zhang; Hongyan Qu; Georgette Gafford; Giji Joseph; Samantha Burton; Leda Bassit; Tysheena P. Charles; et al. (PLoS ONE, 2026)
The lungs are the primary target of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), with the infection resulting in lung inflammation, pulmonary vascular leakage and diffuse alveolar damage. Polymerase delta-interacting protein-2 (Poldip2) mediates lung inflammation and vascular permeability after lipopolysaccharide-induced acute respiratory distress syndrome; however, whether it also affects the pathological consequences of SARS-CoV-2 infection is completely unknown. Here, we assessed the role of Poldip2 in inflammation, immune cell infiltration and lung tissue damage in response to SARS-CoV-2. Our data show that Poldip2 expression was elevated in human lung vascular endothelium after infection. In a Poldip2-deficient heterozygous mouse model, acute clinical symptoms were not affected. However, seven days after infection, Poldip2 knockdown reduced viral load, decreased infiltration of myeloperoxidase (MPO)-positive neutrophils into inflamed lungs, and reduced tissue damage. Poldip2 also modulated the inflammatory response to viral infection in a heterogeneous manner, reflecting its diverse regulatory roles. These data support the concept that targeting Poldip2 could potentially attenuate severe lung injury following SARS-CoV-2 infection.